Nonlinear frequency modulated excitation signal and modified compressing filter for improved range resolution and side lobe level of ultrasound echoes. (15th January 2018) - Dantas, T.M.; Costa-Felix, R.P.B.; Machado, J.C.
Graphical abstract: Highlights: A Compensated Frequency Modulated (CFM) code is used to identify ultrasonic systems. CFM optimizes temporal side lobes for levels below −36 dB. CFM resulted in range resolution better than 0.25 mm. CFM novelty rests on the pseudo-inversion of the system frequency response. Abstract: Purpose: A Compensated Frequency Modulated (CFM) code is proposed as an excitation signal of an ultrasound pulse-echo system. It has a flat envelope and a non-uniform spectral energy density distributed throughout the time span and is tuned to equalize the frequency losses imposed by the system, including the transmitting/receiving electronic instrumentation, the transducer and the propagation medium. The CFM synthesis and the compression filter rely on arbitrary variables, one in determining the CFM spectrum magnitude and the other in determining the spectral magnitude of the compression filter that optimizes the side lobe level and duration (range resolution) of the compressed echo pulse. Methods: The first step is to determine the system transfer function. It is derived from the Fourier transform of an echo signal from a flat reflector, with the transmit/receiving transducer excited by a linear frequency modulated (LFM) signal swept in a frequency range four times the transducer bandwidth, spread symmetrically about the nominal center frequency of the transducer employed in the present work. Experiments were conducted based on a transducer with a half power frequency bandwidth corresponding to 45% of its central frequency and a sweep signal with a time span of 20 µs. Computational simulation was also implemented to determine the effects on the range resolution due to the noise level over the echo signals. Results: The most relevant results in this research are the range resolution as low as 0.23 mm and the maximum temporal lobes below −36 dB. The range resolution obtained with LFM excitation based on the same ultrasonic system setup was on the order of 1.0 mm. Conclusions: The novelty of this approach resides in the pseudo-inversion of the system transfer function magnitude. The combined techniques of CFM pre-filtering and pulse compression mode yielded improved performance in relation to the echo signal duration and temporal side lobes; in addition, a gain of 12 dB over the received echo signal was achieved when using an LFM type excitation signal.